"Nanotracker" for superior early disease diagnosis. Issue 1 (8th August 2022) - Wang, Hanwen; He, Jiahuan; Chen, Guojun
Abstract : Pu and coworkers developed a disease biomarker‐activatable polyfluorophore nanosensor that comprises protease‐reactive peptide brushes, self‐immolative linkers, and renal clearance/tumor‐targeting moiety‐conjugated fluorophore units, for noninvasive near‐infrared fluorescence imaging and urinalysis, enabling superior early disease diagnosis.